2013
DOI: 10.1002/lt.23646
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin A deficiency and vitamin D deficiency in patients evaluated for liver transplantation

Abstract: Background Deficiencies in vitamins A, D and E have been linked to night blindness, bone health, and post-liver transplant reperfusion injury. Aims To determine the prevalence and predictive factors of fat soluble vitamin deficiencies in liver transplantation candidates. Methods We reviewed medical records of liver transplantation candidates at our center from 1/2008–9/2011. Etiology of cirrhosis, MELD scores, Child Pugh class, BMI, vitamin A, vitamin E, and vitamin 25-OH-D levels were recorded. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…In addition, only NASH and the presence of diabetes mellitus independently predicted lower vitamin D levels. These data along with those from others emphasize the importance of insulin resistance on vitamin D levels and that low vitamin D levels can accelerate advanced stages of liver disease. The liver injury associated with low vitamin D concentration may be explained, in part, by a recent study that reported a TGFβ1/Smad3 mediated increase in hepatic profibrotic genes .…”
Section: Discussionsupporting
confidence: 52%
“…In addition, only NASH and the presence of diabetes mellitus independently predicted lower vitamin D levels. These data along with those from others emphasize the importance of insulin resistance on vitamin D levels and that low vitamin D levels can accelerate advanced stages of liver disease. The liver injury associated with low vitamin D concentration may be explained, in part, by a recent study that reported a TGFβ1/Smad3 mediated increase in hepatic profibrotic genes .…”
Section: Discussionsupporting
confidence: 52%
“…Fat soluble vitamin deficiencies are common manifestations of malnutrition and liver disease. 19,20 A retrospective study reported that the majority of liver disease patients being considered for liver transplantation present with vitamin A and D deficiencies. 19 Vitamin A Vitamin A (retinol) is implicated in ocular retinoid metabolism, tissue repair and immunity, and is principally stored in hepatic stellate cells.…”
Section: Vitaminsmentioning
confidence: 99%
“…19,20 A retrospective study reported that the majority of liver disease patients being considered for liver transplantation present with vitamin A and D deficiencies. 19 Vitamin A Vitamin A (retinol) is implicated in ocular retinoid metabolism, tissue repair and immunity, and is principally stored in hepatic stellate cells. As quiescent stellate cells become activated, they lose their vitamin A stores and are then capable of producing collagen and subsequent fibrosis.…”
Section: Vitaminsmentioning
confidence: 99%
“…Thus, it is not surprising that the degree of liver dysfunction correlates with calcidiol levels [3] and that the prevalence of vitamin D insufficiency is particularly high in patients with chronic liver disease [29,30,31,32]. At the time of transplantation, between 80% and 95% of the patients with end-stage liver failure were reported to have hypovitaminosis D, with varying prevalence of severe vitamin D deficiency (ranging from 3% up to 50%) [15,33,34,35]. Notably, in one study, more than one fifth of the patients had serum calcidiol below the detection limit of 6.8 ng/mL [15].…”
Section: Liver Failure and Liver Transplantationmentioning
confidence: 99%